TINJAUAN RELEVANSI CITY BRANDING MELALUI KOLABORASI BRAND INDEX DAN BRAND PERSONALITY: PADANG YOUR MOTHERLAND - Fitri Adona; Sri Nita; Yusnani Yusnani; Lut Mafrudoh (Politeknik Negeri Padang, 2018)
This study applies the collaboration approach of city brand index and city brand personality towards the city branding